The Philippines species of the genus Prothyma Hope, 1838 (Coleoptera: Cicindelidae) Part 1: Subgenera Prothyma Hope, 1838, Genoprothyma Rivalier, 1964 and Parasymplecthyma subgen. nov. - Wiesner, Jürgen; Anichtchenko, Alexander (Zootaxa, 2023)
The Philippines species of Prothyma Hope, 1838 (Prothyma s.str., Genoprothyma Rivalier, 1964 and Parasymplecthyma subgen. nov.) are revised to include 12 species. Prothyma (Genoprothyma) rotundatocuprascens Horn, 1923, and Prothyma (Genoprothyma) confluenteangustata Horn, 1924, are elevated to species rank; Prothyma (Symplecthyma) claudinae Dheurle, 2012 is synonymized with Prothyma (Genoprothyma) tenuipenis Horn, 1934; and two species are described: Prothyma (Genoprothyma) masbateensis sp. nov. and Prothyma (Genoprothyma) miltonmedinai sp. nov. The subgenus Parasymplecthyma subgen. nov., its unique species Prothyma (Parasymplethyma) johnsoni sp. nov. are described. Keys to Prothyma subgenera and to the Philippines species are provided. Color photographs of the habitus and diagnostic characters, also showing their variability, are presented.